Satellite intensity and forbidden reflections from stacking faults in a deformed superalloy - Miller, J. R.; Cole, H. C.; Hogg, J. M.; Pitchforth, J.; Connor, L. D.; Vacek, P.; Neumeier, Steffen; Church, N. L.; Midgley, P. A.; Collins, D. M.; Rae, C. M.F.; Stone, H. J. (Acta Materialia, 2025)
Single crystal Ni-base superalloys, like many materials containing an A1 structured phase, possess additional forbidden reflections in diffraction experiments. These additional reflections are most commonly attributed to the presence of chemical short-range order, or to thin foil effects in transmission electron microscopy. In this study, transmission electron diffraction and synchrotron X-ray diffraction were used to interrogate the deformation mechanics in a single crystal Ni-base superalloy at room temperature. Additional reflections were observed around those from the A1 phase in both diffraction experiments, arising from relrods along 〈111〉*. These relrods were linked to the formation of extensive intrinsic stacking faults (ISFs) within the A1 phase, giving rise to local disorder and a relaxation of the Bragg condition. This study represents the first use of single crystal X-ray diffraction to characterise forbidden reflections in A1 structures from bulk specimens, thereby discounting thin foil effects completely.
CRIS-Team Scopus Importer:2025-10-03
Keywords: Diffraction; Ni-base superalloy; Stacking faults; Synchrotron; TEM